Why be moral? Children's explicit motives for prosocial-moral action - Sengsavang, Sonia; Willemsen, Kayleen; Krettenauer, Tobias (Frontiers in Psychology, 2015)
Recent research on young children's morality has stressed the autonomous and internal nature of children's moral motivation. However, this research has mostly focused on implicit moral motives, whereas children's explicit motives have not been investigated directly. This study examined children’s explicit motives for why they want to engage in prosocial actions and avoid antisocial behavior. A total of 195 children aged 4 to 12 years were interviewed about their motives for everyday prosocial-moral actions, as well as reported on their relationship with their parents. Children's explicit motives to abstain from antisocial behavior were found to be more external and less other-oriented than their motives for prosocial action. Motives that reflected higher levels of internal motivation became more frequent with age. Moreover, positive parent-child relationships predicted more other-oriented motives and greater explication of moral motives. Overall, the study provides evidence that children’s explicit moral motivation is far more heterogeneous than prominent theories of moral development (past and present) suggest.